Effects of Climate Change on Environmental Health in the Jakarta Metropolitan Area - I Alfiansyah; Erlin Dolphina; Aldiana Astuti; Murthada (West Science Nature and Technology, 2023)
This research investigates community perceptions of climate change and its implications for environmental health in the Jakarta Metropolitan Area (JMA) through a quantitative analysis of 150 participants. The study assesses awareness levels, attitudes, and adaptive measures, employing a regression analysis to identify factors influencing climate change awareness. Results reveal a generally high level of awareness, with specific concerns about air and water quality, vector-borne diseases, and perceived threats to overall well-being. The community actively engages in adaptive measures, expressing a desire for increased governmental involvement. The regression analysis highlights age, educational background, and socio-economic status as significant predictors of climate change awareness. These findings provide valuable insights for policymakers, emphasizing the importance of targeted educational campaigns, community engagement initiatives, and addressing awareness disparities to enhance climate resilience in urban settings.